AIAA Guidance, Navigation, and Control Conference 2010
DOI: 10.2514/6.2010-8026
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Dimensional Reduction of a Fuel Optimal Powered Descent Subproblem

Abstract: Current renewed interest in exploration of the moon, Mars, and other planetary objects is driving technology development in many fields of space system design. In particular, there is a desire to land both robotic and human missions on the moon and elsewhere. The landing guidance system must be able to deliver the vehicle to a desired soft landing while meeting several constraints necessary for the safety of the vehicle. Due to performance limitations of current launch vehicles, it is desired to minimize the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The optimal controls are given by Eq. (22), and the corresponding optimal trajectory is very similar to that given in Fig. 7.…”
Section: Optimal Control Problem With a "Soft" Terminal Downrangesupporting
confidence: 64%
See 1 more Smart Citation
“…The optimal controls are given by Eq. (22), and the corresponding optimal trajectory is very similar to that given in Fig. 7.…”
Section: Optimal Control Problem With a "Soft" Terminal Downrangesupporting
confidence: 64%
“…Fuel-optimal control problems formulated with a bounded thrust typically generate thrust profile consists of "bang-bang" type control. [17][18][19][20][21][22] In these optimal thrust solutions, the thrust magnitude "bangs" instantaneously between its maximum and minimum magnitudes. Even ignoring for the time being whether the lunar lander descent engine can be throttled between its minimum and maximum thrust magnitudes instantaneously, we also have a concern about the acceptability of these types of bang-bang control for crew safety.…”
Section: Fig 3 Optimal Control Of a Lander To Ahieve A "Soft" Touchmentioning
confidence: 99%
“…52 Rea and Bishop reduced the dimensionality of the landing problem, assuming constant thrust and a free time-of-flight. 53 Some of the guidance laws have been compared in a trade-off in Ref. 6.…”
Section: Other Methodsmentioning
confidence: 99%
“…The composition of a rotation and translation is represented using dual quaternion multiplication. As such, the unit dual quaternion that represents a translation by r followed by rotation q is given by (taking (11) into account)q…”
Section: B Rigid Body Motionmentioning
confidence: 99%
“…7,8 Several other authors continued to study the necessary conditions of the minimum fuel 3-DoF guidance problem using optimal control theory. [9][10][11] At the same time, Açıkmeşe and Ploen published work with an alternative viewpoint on the 3-DoF problem. [12][13][14] They took a convex programming approach, and showed that a non-convex (non-zero) lower bound on thrust magnitude can be relaxed by introducing a slack variable.…”
Section: Introductionmentioning
confidence: 99%